2016
DOI: 10.1007/s11427-016-5002-0
|View full text |Cite
|
Sign up to set email alerts
|

The two domains of cotton WLIM1a protein are functionally divergent

Abstract: Our previous study demonstrated that WLIM1a has dual roles in fiber elongation and secondary cell wall synthesis in upland cotton, and the protein acts either as an actin-binding protein or as a transcription factor. Because WLIM1a consists of two different LIM domains, it is possible that these elements contribute differentially to the dual functions of the protein. In this study, we dissected the two LIM domains and characterized their biochemical functions. By using red fluorescent protein (RFP) fusion, co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, more variation was found in their C‐terminal LIM domain. Recently, a study indicated that the N‐terminal LIM domain contributes primarily to the F‐actin bundling activity of GhWLIM1a, but the C‐terminal LIM domain contributes to the DNA‐binding activity (Han et al ., ). So, the difference sequence between GhWLIM1a and GhXLIM6 C‐terminal LIM domain may lead to their functional differentiation in fiber cell development.…”
Section: Discussionmentioning
confidence: 97%
“…However, more variation was found in their C‐terminal LIM domain. Recently, a study indicated that the N‐terminal LIM domain contributes primarily to the F‐actin bundling activity of GhWLIM1a, but the C‐terminal LIM domain contributes to the DNA‐binding activity (Han et al ., ). So, the difference sequence between GhWLIM1a and GhXLIM6 C‐terminal LIM domain may lead to their functional differentiation in fiber cell development.…”
Section: Discussionmentioning
confidence: 97%
“…A typical plant LIM protein contains two LIM domains, and the two domains were shown to occupy different actin affinities. For example, LIM1 of cotton WLIM1a protein contributed primarily to the actin filament-bundling activity, whereas LIM2 contributed to the DNA-binding activity of the protein [ 36 ]. Differently from our experiment, it seems that both LIM1 and LIM2 of GhWLIM1C could bind to the actin filaments ( Figure 3 B,C; Figure 5 B,C); while LIM1 only possesses actin-binding activity ( Figure 5 B), LIM2 could directly bind and bundle actin filaments ( Figure 5 C).…”
Section: Discussionmentioning
confidence: 99%
“…Plant LIM proteins are another important class of ABPs [ 65 ], which are found to be dispersed in the cytosol and nucleoplasm. The LIM-domain-containing proteins in the nucleus are preferentially involved in tissue-specific gene regulation and determination of cell fate, whereas the cytoplasmic LIM-domain-containing proteins are involved mainly in cytoskeletal organization [ 66 ]. The term “LIM” originates from the initials LIN-11, ISL-1, and MEC-3, the first proteins observed to contain this particular homeodomain.…”
Section: Role Of Actin Genes In Cotton Fiber Devel...mentioning
confidence: 99%